2014
DOI: 10.1371/journal.pone.0108787
|View full text |Cite
|
Sign up to set email alerts
|

How Are Health Research Priorities Set in Low and Middle Income Countries? A Systematic Review of Published Reports

Abstract: BackgroundPriority setting is increasingly recognised as essential for directing finite resources to support research that maximizes public health benefits and drives health equity. Priority setting processes have been undertaken in a number of low- and middle-income country (LMIC) settings, using a variety of methods. We undertook a critical review of reports of these processes.Methods and FindingsWe searched electronic databases and online for peer reviewed and non-peer reviewed literature. We found 91 initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
156
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 32 publications
3
156
0
11
Order By: Relevance
“…For anyone interested in setting health research priorities at any level, I recommend several comprehensive reviews of the principles, methods, approaches and tools [3,[7][8][9][10][11]. Based on those readings, it should become apparent that the CHNRI method proposed its own definition of health research.…”
Section: Setting Health Research Priorities: Universal Challenges Andmentioning
confidence: 99%
See 1 more Smart Citation
“…For anyone interested in setting health research priorities at any level, I recommend several comprehensive reviews of the principles, methods, approaches and tools [3,[7][8][9][10][11]. Based on those readings, it should become apparent that the CHNRI method proposed its own definition of health research.…”
Section: Setting Health Research Priorities: Universal Challenges Andmentioning
confidence: 99%
“…Two recent reviews showed that the CHNRI method has become the dominant approach to setting health research priorities in the global biomedical literature over the past decade [9,10]. Its applications have been helpful in promoting better balance between investments in fundamental research, translation research and implementation research.…”
mentioning
confidence: 99%
“…Stakeholder engagement, and data and capacity constraints frequently impeded the process for setting priorities, more so in the LMICs [16]. The current exercise, through systematic inclusion of diverse range of national stakeholders in a LMIC setting, identified priorities for maternal, neonatal and child health and nutrition at national and sub–national (regional) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Una estrategia para lograrlo es que la investigación en salud esté orientada por prioridades de investigación consensuadas e identificadas de manera participativa entre los principales actores del sistema nacional de investigación (3) . En ausencia de prioridades, existe la posibilidad que, en estos países, la investigación pueda responder a necesidades de los financiadores o de los intereses propios de los investigadores, muchas veces diferentes a las necesidades del país (4,5) .…”
Section: Introductionunclassified